Development of insulin-sensitivity at weaning in the rat. Role of the nutritional transition. - Issad, T (1988)
This study was undertaken to determine the factors involved in the development of insulin-sensitivity at weaning. Glucose kinetics were studied in suckling rats and in rats weaned on to a high-carbohydrate (HC) or a high-fat (HF) diet, in the basal state and during euglycaemic-hyperinsulinaemic-clamp studies. These studies were coupled with the 2-deoxyglucose technique, allowing a measure of glucose utilization by individual tissues. In the basal state, the glycaemia was higher in HF-weaned rats (124 +/- 4 mg/dl) than in suckling (109 +/- 1 mg/dl) and HC-weaned rats (101 +/- 3 mg/dl). Glucose turnover rates were similar in the three groups of animals (14 mg/min per kg). Nevertheless, basal metabolic glucose clearance rate was 20% lower in HF-weaned rats than in the other groups. During the euglycaemic-hyperinsulinaemic experiments, hepatic glucose production was suppressed by 90% in HC-weaned rats, whereas it remained at 40% of basal value in suckling and HF-weaned rats, indicating an insulin resistance of liver of these animals. Glucose clearance rate during the clamp was 18.3 +/- 0.9 ml/min per kg in suckling rats, whereas it was 35.3 +/- 1.2 ml/min per kg in HC-weaned rats and 27.8 +/- 1.1 ml/min per kg in HF-weaned rats, indicating an insulin resistance of glucose utilization in suckling, and to a lower extent, in HF-weaned rats. The deoxyglucose technique showed that peripheral insulin resistance was localized in muscles and white adipose tissue of suckling and HF-weaned rats. These results indicate that the switch from milk to a HC diet is an important determinant of the development of insulin-sensitivity at weaning in the rat.